The Role of The Intra School Student Organization in Fostering Civic Skills at SMAN 1 Gunungsai, Lombok Barat - Sulissawati Sulissawati; M. Mabrur Haslan; Sawaludin Sawaludin; L. Sumardi (Jurnal Penelitian Medan Agama, 2026)
The Intra-School Student Organization (OSIS) is an organization that forms part of extracurricular activities and plays an important role in developing students’ civic skills at school. This study aimed to examine the development of students’ civic skills through OSIS activities and to identify the internal and external factors influencing their development at SMAN 1 Gunungsari. This study employed a qualitative approach with a descriptive research design. Data were collected through observation, interviews, and documentation. The findings revealed that several civic skills were developed through OSIS activities, including problem-solving, critical thinking, decision-making, teamwork, and communication skills. OSIS activities that supported the development of civic skills included: (1) Basic Student Leadership Training (LDKS), which developed self-confidence, communication skills, social awareness and responsibility, organizational enthusiasm, and environmental awareness; (2) flag ceremonies, which fostered discipline, responsibility, compliance with rules, respect for national symbols, and patriotism; (3) class meetings, which promoted cooperation and solidarity, sportsmanship, a competitive spirit, responsibility, and leadership; and (4) community service activities, which encouraged cooperation, social awareness, and environmental awareness.